2014
DOI: 10.5455/musbed.20140428120946
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in Preeclampsia: Function and Role in the Inflammation

Abstract: Preeklampside trombositlerin enflamasyondaki rolü ve etkileriPreeklampsi tüm gebeliklerin %5-8' ini komplike eden gebeliğin hipertansif hastalığıdır. Preeklampsi patogenezinde kılcal damar yatağındaki inflamasyon önemli rol oynar. Preeklampside olduğu gibi dolaşımda serbest halde bulunan mikropartiküllerle trombositlerin karşılaşması sonucunda trombositler aktive olurlar. Aktive olan trombositler dolaşıma serbest moleküller salarlar ve hücre yüzeylerindeki adhezyon moleküllerinin artmasına neden olurlar. Serbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Enhanced thrombopoiesis produces younger and larger platelets that are metabolically and enzymatically more active [ 12 , 13 ]. The inflammatory response is intensified in pre-eclampsia by the induction of inflammatory cytokines by adherent platelets on endothelial cells culminating in severe hemostatic, vascular, and coagulation abnormalities that cause serious feto-maternal complications [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced thrombopoiesis produces younger and larger platelets that are metabolically and enzymatically more active [ 12 , 13 ]. The inflammatory response is intensified in pre-eclampsia by the induction of inflammatory cytokines by adherent platelets on endothelial cells culminating in severe hemostatic, vascular, and coagulation abnormalities that cause serious feto-maternal complications [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular development is influenced by PECAM-1 through the formation of a complex with VEGFR-2 and VE cadherin [35]. In PE, PECAM-1 induces neutrophil and platelet activation, thereby promoting vascular damage [36]. Thakoordeen et al (2017) demonstrated a similar level of PECAM-1 between control and preeclamptic pregnancies ( p = 0.07), while no correlation was found based on HIV infection ( p = 0.68) or across study groups ( p = 0.24) [37].…”
Section: Angiogenesismentioning
confidence: 99%
“…Healthy vascular endothelium secretes several mediators such as nitric oxide (NO), and adenosine which inhibits platelet activation, adhesion to endothelium. 2,13 However, inflammation of the endothelium results in the production of these protective mediators being reduced. NO and adenosine metabolites are increased in pre-eclampsia patients in parallel to significant platelet activation compared with normotensive pregnancies.10 Lyall et al demonstrated that NO concentrations are increased in the feto-placental circulation in preeclampsia.…”
Section: Platelet Levelsmentioning
confidence: 99%
“…They also suggest that elevated NO levels further complement platelet activation in preeclamptic women. 13 Circulating platelets are exposed to soluble factors such as lipid mediators, cytokines, and chemokines which are released by activated leukocytes and endothelial cells due to inflammation of the blood vessels. The accumulation of these mediators gives rise to an activation response characterized by degra-nulation of platelet granules.…”
Section: Platelet Levelsmentioning
confidence: 99%